Miscellaneous

Misc 1

Misc 2

Misc 3

Misc 4

Misc 5 Important

Misc 6 Important

Misc 7 Important

Misc 8

Misc 9 Important

Misc 10

Misc 11 Important

Misc 12

Misc 13 Important

Misc 14 Important

Misc 15 Important

Misc 16 Important

Misc 17 Important

Misc 18

Misc 19

Misc 20

Misc 21

Misc 22 Important

Question 1 Important Deleted for CBSE Board 2025 Exams You are here

Last updated at April 16, 2024 by Teachoo

Question 1 Using mathematical induction prove that 𝑑/𝑑𝑥(𝑥^𝑛) = 〖𝑛𝑥〗^(𝑛−1) for all positive integers 𝑛. Let 𝐏(𝒏) : 𝑑/𝑑𝑥 (𝑥^𝑛) = 〖𝑛𝑥〗^(𝑛−1) For 𝒏 = 𝟏 Solving LHS (𝑑(𝑥^1)" " )/𝑑𝑥 = 𝑑𝑥/𝑑𝑥 = 1 = RHS Thus, 𝑷(𝒏) is true for 𝑛 = 1 Let us assume that 𝑷(𝒌) is true for 𝑘∈𝑵 𝑷(𝒌) : (𝑑 (𝑥^𝑘))/𝑑𝑥 = 〖𝑘 𝑥〗^(𝑘−1) Now We have to prove that P(𝒌+𝟏) is true 𝑃(𝑘+1) : (𝑑(𝑥^(𝑘 + 1))" " )/𝑑𝑥 = 〖(𝑘+1) 𝑥〗^(𝑘 + 1 − 1) (𝑑(𝑥^(𝑘 + 1)))/𝑑𝑥 = 〖(𝑘+1) 𝑥〗^𝑘 Taking L.H.S (𝑑(𝑥^(𝑘 + 1)))/𝑑𝑥 = (𝑑(𝑥^(𝑘 ). 𝑥))/𝑑𝑥 Using product rule As (𝑢𝑣)’ = 𝑢’𝑣 + 𝑣’𝑢 where u = xk & v = x = (𝑑(𝑥^𝑘)" " )/𝑑𝑥 . 𝑥 + 𝑑(𝑥 )/𝑑𝑥 . 𝑥^(𝑘 ) = (𝒅(𝒙^𝒌)" " )/𝒅𝒙 . 𝑥 + 1 . 𝑥^(𝑘 ) = (〖𝒌. 𝒙〗^(𝒌−𝟏) ) . 𝑥+𝑥^𝑘 = 〖𝑘. 𝑥〗^(𝑘−1 + 1) .+𝑥^𝑘 = 〖𝑘. 𝑥〗^𝑘+𝑥^𝑘 = 𝑥^𝑘 (𝑘+1) = R.H.S Hence proved (From (1): (𝑑(𝑥^𝑘 ") " )/𝑑𝑥 = 〖𝑘 𝑥〗^(𝑘−1) ) Thus , 𝑷(𝒌+𝟏) is true when 𝑷(𝒌) is true Therefore, By Principle of Mathematical Induction 𝑃(𝑛) : 𝑑/𝑑𝑥 (𝑥^𝑛) = 〖𝑛𝑥〗^(𝑛−1) is true for all 𝑛∈𝑵